Peran Penyuluh Agama Islam dalam Pembuatan Sertifikat Halal bagi UMKM Makanan dan Minuman di Indonesia - Arin Herlawati Wijaya; Dian Tias Aorta (Universitas Palangka Raya, 2026)
This study explores the urgency of halal certification for food and beverage Micro, Small, and Medium Enterprises (UMKM) in Indonesia following the implementation of Law Number 33 of 2014. Despite the enactment of regulations, various obstacles such as low halal literacy and bureaucratic complexity remain major challenges. This study aims to analyze the strategic role of Islamic religious instructors as agents of empowerment and da'wah (Islamic outreach) in assisting UMKM in their halal certification process. Using qualitative methods with a library research approach, data was collected through a search of relevant literature and regulations, then analyzed using content analysis techniques. The study results indicate that Islamic religious instructors perform four crucial functions: literacy educators, access facilitators, motivators of Islamic economics, and policy mediators. Optimizing these roles can be achieved through capacity building, digitalization of mentoring, and integration of community networks. The study concludes that strengthening the role of instructors is essential to accelerate the implementation of mandatory halal certification and strengthen the Islamic economic ecosystem in Indonesia.